2022
DOI: 10.3390/jcm11144054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bariatric Surgery on Flow-Mediated Vasodilation as a Measure of Endothelial Function: A Systematic Review and Meta-Analysis

Abstract: Objectives. Flow mediated vasodilation (FMD) is a marker of endothelial function and its decline is related to increased cardiovascular risk. This systematic review and meta-analysis evaluated the impact of bariatric surgery on FMD. Materials and methods. A systematic literature search in PubMed, Scopus, Embase, and Web of Science was performed to 1 May 2021. Meta-analysis was performed using Comprehensive Meta-Analysis (CMA) V2 software. All types of bariatric surgery were considered, with the inclusion that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…This is the first meta-analysis evaluating the impacts of bariatric surgery on PCSK9 as a regulator of plasma cholesterol levels. This finding is consistent is with other reports suggesting a positive impact of bariatric surgery on cardiovascular risk factors (17)(18)(19)(20). The observed drop in circulating PCSK9 levels could be attributed to long-term weight loss caused by bariatric procedure as well as sustained decreases in total food intake (11).…”
Section: Effect Of Bariatric Surgery On Pcsk9 and Ldl-csupporting
confidence: 92%
“…This is the first meta-analysis evaluating the impacts of bariatric surgery on PCSK9 as a regulator of plasma cholesterol levels. This finding is consistent is with other reports suggesting a positive impact of bariatric surgery on cardiovascular risk factors (17)(18)(19)(20). The observed drop in circulating PCSK9 levels could be attributed to long-term weight loss caused by bariatric procedure as well as sustained decreases in total food intake (11).…”
Section: Effect Of Bariatric Surgery On Pcsk9 and Ldl-csupporting
confidence: 92%
“…A recent meta-analysis showed that obese patients who had undergone bariatric surgery had significant improvement in endothelial function ascertained by increasing FMD measurements, independent of the weight loss, suggesting that weight-independent mechanisms such as endocrine and incretin-mediated effects and improved inflammatory status might contribute as well to the amelioration of ED [ 90 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Weight loss has beneficial effects on the main risk factors for ASCVD including elevated total and LDL-cholesterol (LDL-C), triglycerides, and decreased HDL-cholesterol (HDL-C) [6]. Bariatric surgery has beneficial effects on cardiovascular indices [7][8][9]. For instance, it has been shown that gastric bypass surgery improved all lipid profile parameters, although sleeve gastrectomy only improved HDL-C and triglyceride levels [10,11].…”
Section: Introductionmentioning
confidence: 99%